Hubungan Persalinan Jampersal Dengan Kepuasan Ibu Bersalin Di Puskesmas - Dony Putra (Jurnal Kesehatan dr. Soebandi, 2020)
Patient satisfaction is a patient's level of feeling which arises as a result of the performance of the service she gets after he compared it with what she hoped. This research aimed to find out Jampersal relationship with maternal satisfaction working area Curahdami health centers, Bondowoso Regency in 2013. Research design was used correlation study with Cross-Sectional approach. Population in this research is mother who ever give birth at health centers Curahdami working area, in January-June 2013 as many as 100 people, with a sample of 80 people using Simple Random Sampling technique. The results showed that maternals who were satisfied with the maternity Jampersal as many as 49 people, and which are not satisfied as many as 31 people. Data obtained then analyzed using Chi Square one count samples were obtained χ2 > χ2 table is 4.05 > 3.841 where KK 0.22. So that the null hypothesis (Ho) is rejected and the alternative hypothesis (Ha) is accepted, which means there is Jampersal labor relations with maternal satisfaction working area Curahdami health centers Bondowoso regency in 2013. by improving service quality, will affect maternal satisfaction it means she will feel satisfied because obtaining a good or service with what she hoped, the better quality of health care given, the more perfect satisfaction